The public sector accounting, accountability and auditing in emerging economies - Jayasinghe, Kelum; Nath, Nirmala; Othman, Radiah (Emerald, 2015)
This volume aims to contribute to the substance of this debate by looking at how the NPM ideas have been conceptualised, implemented and affected the accounting, accountability and auditing practices in emerging economies characterised by different ideologies, economic, social and political factors. The NPM-led furore, based on the assumption of a leaner public sector, has hit the emerging economies; the outcomes of this in emerging economies have not yet been either researched or hugely publicised. In accounting, studies that relate and appreciate the history and its ideological significance are under-emphasized; henceforth this issue bridges the gap and focuses on studies that historically examine the development of accounting, accountability and auditing in the emerging economies, pre-and post NPM.
Keywords: Business & Economics -- Accounting -- General.; Accounting.; Public finance accounting.; Finance, Public -- Accounting.; Public administration.; Economic development.; elektronické knihy; electronic books